# a function f(x) satisfies the equation f(x)=f(x-1)+f(x+1) for all values of x. Define f(1)=1 and f(3)=3; then f(2)=1+3=4. find f(1867)?

### 1 Answer

Relevance

- micatkieLv 64 weeks agoFavorite Answer
It is given that: f(x) = f(x - 1) + f(x + 1)

Add two more consecutive relations:

f(x + 1) = f(x) + f(x + 2) …… [1]

f(x + 2) = f(x + 1) + f(x + 3) …… [2]

[1] + [2]: f(x) + f(x + 3) = 0 …… [3]

Also: f(x + 3) + f(x + 6) = 0 …… [4]

[3] - [4]:

f(x) - f(x + 6) = 0

f(x + 6) = f(x)

Similarly, f(x + 12) = f(x + 6)

f(x + 18) = f(x + 12)

…… and so on

It can be deduced that f(x + 6n) = f(x)

where n is an integer.

f(1867)

= f(1 + 6×311)

= f(1)

= 1

Still have questions? Get your answers by asking now.